2022
DOI: 10.1088/1361-6463/ac5f32
|View full text |Cite
|
Sign up to set email alerts
|

The state of the art of Sb2(S, Se)3 thin film solar cells: current progress and future prospect

Abstract: In this work, a review focused on the recent development of antimony sulfide selenide (Sb2(S,Se)3) solar cells is presented. In particular, experimental and theoretical results are discussed to understand the current limiting factors of this technology, as well as possible routes for device promotion. The Sb2(S,Se)3 compound is introduced as an attractive compound for single junction and multijunction solar cells since it is described by a band-gap that can be tailored in the range of 1.1 – 1.8 eV. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 88 publications
(138 reference statements)
3
15
0
Order By: Relevance
“…10 Because of its environmental friendliness and high absorption coefficient (10 5 cm −1 ), antimony triselenide (Sb 2 Se 3 ) has become a particularly attractive light absorber for solar cells in recent years. 11 In accordance with the Shockley−Queisser limit, the maximal PCE of a single-junction Sb 2 S 3 solar cell can achieve 28.64%, pending its large band gap (1.7 eV). 12 Consequently, it is a potential candidate for tandem solar cell utilization.…”
Section: ■ Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…10 Because of its environmental friendliness and high absorption coefficient (10 5 cm −1 ), antimony triselenide (Sb 2 Se 3 ) has become a particularly attractive light absorber for solar cells in recent years. 11 In accordance with the Shockley−Queisser limit, the maximal PCE of a single-junction Sb 2 S 3 solar cell can achieve 28.64%, pending its large band gap (1.7 eV). 12 Consequently, it is a potential candidate for tandem solar cell utilization.…”
Section: ■ Introductionmentioning
confidence: 86%
“…Sb 2 Se 3 -based solar cells have indicated better performance since dominant efficiency values of 3.21 and 2.26% (laboratory scale) were achieved in 2014 . Because of its environmental friendliness and high absorption coefficient (10 5 cm –1 ), antimony triselenide (Sb 2 Se 3 ) has become a particularly attractive light absorber for solar cells in recent years . In accordance with the Shockley–Queisser limit, the maximal PCE of a single-junction Sb 2 S 3 solar cell can achieve 28.64%, pending its large band gap (1.7 eV) .…”
Section: Introductionmentioning
confidence: 99%
“…Numerical solutions of basic semiconductor equations can be solved using SCAPS-1D software, which shows the performance parameters of the Sb 2 Se 3 solar cell [37][38][39]. The SCAPS-1D continuity equation and Poisson equation must be solved for minority charge carriers (i.e., holes and electrons) to understand the Sb2Se3 solar cell device better.…”
Section: Proposed Solar Cell Software and Numerical Simulationmentioning
confidence: 99%
“…On the other hand, previous works have shown that major important problems concerning FTO/CdS/Sb 2 (Se 1-x S x ) 3 / Spiro-OMeTAD/Au solar cells are the formation of defects at CdS (ETL)/Sb 2 (S,Se) 3 and Spiro-OMeTAD (HTL)/Sb 2 (S,Se) 3 interfaces, resulting in charge carrier losses. [18,19] In this sense, new ETL and HTL materials that result in lower defect formation at interfaces as well as better band alignment for carrier transport are needed to promote Sb 2 (S,Se) 3 -based solar cell efficiency.…”
Section: Introductionmentioning
confidence: 99%